Chemical composition of pyrolysis oil through thermal decomposition of sugarcane biomass - Huynh Van Nam; Dinh Quoc Viet; Truong Thanh Tam; Van Dinh Son Tho (My University, 2020)
Chemical composition of pyrolysis oil through thermal decomposition of sugarcane biomass
Keywords: Dầu nhiệt phân